2021
DOI: 10.3390/cells10030579
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Drosophila melanogaster Research to UnCover Cellular Pathways Underlying Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a complex neurodegenerative disorder that is currently incurable. As a consequence of an incomplete understanding of the etiology of the disease, therapeutic strategies mainly focus on symptomatic treatment. Even though the majority of PD cases remain idiopathic (~90%), several genes have been identified to be causative for PD, facilitating the generation of animal models that are a good alternative to study disease pathways and to increase our understanding of the underlying mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 206 publications
1
12
0
Order By: Relevance
“…However, similar mechanisms are present in both sporadic and genetic forms of the disease. Studies on drug abusers with parkinsonism have hinted towards defects at the level of the mitochondrial electron transport chain, which was later confirmed in patients and animal models [ 66 , 67 , 68 , 69 , 70 ]. Furthermore, PINK1-dependent phosphorylation is required for an efficient ETC, and the stimulation of the ETC can alleviate signs in pink1- and drug-related PD animal models [ 71 , 72 , 73 ].…”
Section: Parkinson’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…However, similar mechanisms are present in both sporadic and genetic forms of the disease. Studies on drug abusers with parkinsonism have hinted towards defects at the level of the mitochondrial electron transport chain, which was later confirmed in patients and animal models [ 66 , 67 , 68 , 69 , 70 ]. Furthermore, PINK1-dependent phosphorylation is required for an efficient ETC, and the stimulation of the ETC can alleviate signs in pink1- and drug-related PD animal models [ 71 , 72 , 73 ].…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…Interestingly, mitochondrial symptoms have been observed in other genetic PD models, including alpha-synuclein-dependent models [ 79 ], suggesting that mitochondrial dysfunction plays an important role in the pathogenesis of PD; however, the underlying mechanisms of how mitochondrial dysfunction results in neurodegeneration remains enigmatic. A more recently identified pathway that is linked to PD is the endo-lysosomal pathway, in which the autosomal dominant PD-related genes play a major role [ 70 ]. Alpha-synuclein and LRRK2 are linked to Rab proteins, which are important in the endo-lysosomal pathway [ 80 , 81 ].…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…Although non-human primates most closely mimic the human pathology, mice are the most often used animal model [ 11 ]. The neuronal overexpression of human αSyn in mouse neurons can be associated with αSyn aggregation and locomotor impairment although the loss of dopaminergic neurons is often not observed [ 12 ]. For example, it was shown that misfolded and hyperphosphorylated αSyn that are resistant to proteinase K digestion are found in transgenic mice with motor deterioration [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several models of PD were developed in Drosophila , including a well-characterized model in which the neuronal overexpression of human SNCA gene using the UAS/GAL4 system mimics PD hallmarks [ 19 ]. This model was greatly used to study and characterize conserved cellular mechanisms associated with αSyn pathology in humans, despite the fact that Drosophila does not carry an endogenous ortholog of SNCA gene [ 12 , 20 , 21 ]. The common parkinsonian hallmarks observed in flies overexpressing SNCA include the accumulation of αSyn aggregates in situ, loss of dopaminergic neurons (DA), and the impairment of fly locomotion (negative geotaxism) [ 17 , 19 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, in the last few decades, immense research efforts have revealed several mechanisms that are affected in PD, including mitochondrial abnormalities. 3 …”
mentioning
confidence: 99%